DETERMINASI BELANJA DAERAH PADA KABUPATEN MUSI BANYUASIN: DARI PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS - Annisah Yuni Fakhirah; Bainil Yulina; Husni Mubarok (Politeknik Negeri Sriwijaya, 2022)
This study aims to determine the effect of Regional Original Income, General Allocation Funds, Special Allocation Funds on Regional Expenditures in Musi Banyuasin Regency in 2015-2019. This study uses quantitative data type. The sample used in this study is a total/saturated sample which includes 15 sub-districts in Musi Banyuasin Regency. This study uses multiple regression analysis with the help of SPSS version 26 application. The result of this study indicate that (1) Regional Original Income has a positive and significant effect on Regional Expenditures, (2) General Allocation Funds has a positive and significant effect on Regional Expenditures, and (3 ) Special Allocation Funds have a positive and significant effect on Regional Expenditures (4) Regional Original Revenue, General Allocation Funds, and Special Allocation Funds simultaneously have a positive and significant effect on Regional Expenditures with a determination coefficient of 45.6%.